2022
DOI: 10.3390/ijerph192215066
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Degradation and Microbial Survival Improvement in Response to γ-Polyglutamic Acid Application

Abstract: To improve the environmental sustainability of cleanup activities of contaminated sites there is a need to develop technologies that minimize soil and habitat disturbances. Cleanup technologies, such as bioremediation, are based on biological products and processes, and they are important for the future of our planet. We studied the potential of γ-poly glutamic acid (PGA) as a natural component of biofilm produced by Bacillus sp. to be used for the decomposition of petroleum products, such as heavy naphtha (N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The Ambiogel ® (Ambioteco Sp. z o.o., Staszów, Poland) containing 5% of pure poly-γ-glutamic acid with varying molecular mass (2000–1000 kDa—30%; 1000–140 kDa—50%; 100 kDa–300 Da—15%; <300 Da—5%) was used as a γ-PGA additive [ 130 ]. The phytoremediation tests used seeds of maize ( Zea mays ) (Legutko, Poland) planted in pre-treated soil (after completing biodegradation tests using inoculation with biopreparations) in May 2022.…”
Section: Methodsmentioning
confidence: 99%
“…The Ambiogel ® (Ambioteco Sp. z o.o., Staszów, Poland) containing 5% of pure poly-γ-glutamic acid with varying molecular mass (2000–1000 kDa—30%; 1000–140 kDa—50%; 100 kDa–300 Da—15%; <300 Da—5%) was used as a γ-PGA additive [ 130 ]. The phytoremediation tests used seeds of maize ( Zea mays ) (Legutko, Poland) planted in pre-treated soil (after completing biodegradation tests using inoculation with biopreparations) in May 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the use of γ-PGA as an additive to microbial consortia made it possible to provide the plant with a readily available source of carbon and energy, which further influenced biomass production. It is also worth noting that some literature sources report that γ-PGA can be considered a biosurfactant, which affects the diffusion of xenobiotics into the root [17,62,64,75]. Chromatographic analyses of the roots and shoots showed that extraction of aliphatic hydrocarbons from the soil to the root occurred most readily in systems 4 and 5, and 10 and 11.…”
Section: Analysis Of Petroleum Hydrocarbons In Soil Root and Shootmentioning
confidence: 96%
“…More information about the microbial consortia used in the research is available in Supplementary Materials. A commercially available formulation of Ambiogel ® (Ambioteco, Staszów, Poland) containing 5% pure poly-γ-glutamic acid [64], whose impact on the efficiency of bioremediation has been confirmed in earlier studies, was used as an additive for microbial consortia. The phytoremediation process was carried out using seeds of Echinacea purpurea (Legutko, Poland), which were sown in each of the tested systems.…”
Section: Soil Microbial Consortia γ-Pga and Plant Descriptionmentioning
confidence: 99%